BANK ISLAM DAN HARAPAN UMAT (Studi Atas Kelebihan Bank Islam) - Zainuddin, Muhadi (Islamic University of Indonesia, 2003)
Bank practices that practice by commercial banks canât be free from materialistic capitalism. Those practices has made social problems that threaten human civilization. The hidden âpoorâ processing has been running body and spiritual. It happens because human faces materialistic business. Their dream about developing of economy canât make true because unemployment and recession. Thatâs why, Economic Moslems try to formulate economy systems that keep away from negative effects to human civilization. They found mistakes from ways of thinking in modem society. Materialistic capitalism paradigm has got weakness, and serious effects -for moral crisis. It makes human is like machines that doesnât care about his existence in social things. If they do what we call social things, of course it is not only than save his individualistic-ego. This paper tries to find those problems, and of course to give the results. It needs to other chosen about conventional bank institute that works is based on materialistic capitalism, because it is only producing social problems. It bases on histories Rosulullohs rules that managed financial system in his time, and tried to find Allahâs message in His verses. Those economist find âmetafora amanahâ (instruction metaphore) as its a paradigm. Thatâs why Islamic bank is really suitable to have more position than conventional bank. Of course Itâs âmetafora amanahâ (instruction metaphore) can have more positive effects of ideology from Islamic economy, and itâs specially for bank system. Itâs based on this system, of course, human can have balance between individualâs rule and socialâs rules. By this concept, Islamic bank, by operational transactions, will have more benefits than other conventional bank. Islamic bank make clear of all transactions, more transparent, far away from exploring from one side and manipulation, and accountable. Finally, those benefits will give good effects for society, because this orientation will give good corporate and sharing.